2003
DOI: 10.1097/01.psy.0000041472.77692.c6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Pain Significantly Increase Before Death in Metastatic Breast Cancer Patients

Abstract: Results suggest that specialized end-stage clinical interventions are particularly needed for cancer patients as they approach death. Moreover, intervention studies for patients with deteriorating illnesses may need to take this "spike" in psychological distress and pain proximal to death into account to avoid Type II errors in evaluations of psychological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 30 publications
4
50
0
10
Order By: Relevance
“…Nonmetastatic breast cancer patients have pain prevalence rates of 33% to 52%; the rate increases to 56% -68% among women with metastatic breast cancer (McGuire & Sheidler, 1992). Pain is a primary symptom of breast cancer when there is bone metastasis (Dow, Ferrell, Leigh, Ly , & Gulasekaram, 1996), and may increase over the course of metastatic illness, particularly in the period prior to death (Butler et al, 2003). Sleep disturbances are almost universal for people with chronic pain (McCracken & Iverson, 2002).…”
Section: Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonmetastatic breast cancer patients have pain prevalence rates of 33% to 52%; the rate increases to 56% -68% among women with metastatic breast cancer (McGuire & Sheidler, 1992). Pain is a primary symptom of breast cancer when there is bone metastasis (Dow, Ferrell, Leigh, Ly , & Gulasekaram, 1996), and may increase over the course of metastatic illness, particularly in the period prior to death (Butler et al, 2003). Sleep disturbances are almost universal for people with chronic pain (McCracken & Iverson, 2002).…”
Section: Painmentioning
confidence: 99%
“…Therefore, we included the baseline intercept of the sleep variables as a covariate in each multiple regression analysis because the intercept is the best estimate of the true baseline value of the variable. Previous research has shown that women with metastatic breast cancer report a significant increase in distress and pain prior to dying (Butler et al, 2003;Classen, Butler, Koopman, Miller, DiMiceli, Giese-Davis, Fobair et al, 2001). Consequently, we dropped assessment that was proximal to death (within 12 months) and recalculated the slopes based on the remaining points.…”
mentioning
confidence: 99%
“…Genau das erwartet man auch von einer supportiv-expressiven Gruppenintervention, da sie die Konfrontation mit den existenziellen Herausforderungen und die Verbesserung der emotionalen Expressivität fördert (Butler et al 2003;Classen et al 2001). Diese Art der Intervention führt zu signifikanten Verschiebungen in der emotionalen Regulation, die sich in signifikanten Verbesserungen der emotionalen Expressivität zeigen: Die Unterdrückung von negativem Affekt wird reduziert, einhergehend mit verbesserter Selbstkontrolle im Ausdruck von Feindseligkeit, antagonistischen und sozial entfremdenden Verhaltensweisen (Giese-Davis et al 2002).…”
Section: Gruppentherapie Für Frauen Mit Metastasierendem Brustkrebsunclassified
“…Zugleich scheint es unklug, Kurz-Zeit-Gruppen in der Pflege von schwer kranken und sterbenden Patientinnen einzurichten. Stattdessen sollte man weiter die Möglichkeit von "Openend-Behandlungen" untersuchen mit speziell ausgearbeiteten Interventionen für Frauen, deren Tod naht (Butler et al 2003). …”
Section: Gruppentherapie Für Frauen Mit Metastasierendem Brustkrebsunclassified
“…Pain is a feared and common complication in patients with cancer (1,2), which increases in prevalence and intensity with disease progression (3,4), and influences multiple aspects of quality of life (5)(6)(7)(8). Pharmacogenetic, pharmacokinetic and pharmacodynamic variations among individuals result in a wide variety of responses to pain sensation and analgesics; therefore, investigations of biomarkers for opioid treatment have been performed to improve the efficacy of morphine treatment (9).…”
Section: Introductionmentioning
confidence: 99%